Parasitos e comensais intestinais em pacientes neoplásicos submetidos à quimioterapia - Silva, Luciana Pereira [UNESP]; Fernandes, Natália Amendola [UNESP]; Oliveira, José Aparecido Alves de; Silva, Regildo Márcio Gonçalves da [UNESP] (My University, 2011)
The objective of this study was to verify the prevalence of intestinal parasites and/or commensals in the neoplastic patients undergoing chemotherapy. Stool samples were analyzed by the method of Lutz (1919) and Rugai (1954), in triplicate. This work was composed of three groups, the first one (GI) formed by neoplastic patients that are not undergoing chemotherapy, the second (GII) comprised patients who were undergoing chemotherapy, and the third group (GIII) consisting of patients who completed chemotherapy. A total of 30 patients (GI-5, GII-18 and GIII-7) were screened at the Assis Regional Hospital of the Unified Health System of Assis, São Paulo.Additional information on antiparasitic treatment and tumor type were obtained by questionnaire. The positivity was 66.7% (20 cases) for intestinal parasites and/or commensals. The helminths were Ascaris lumbricoides (36.7%), Hookworms (20%) and Hymenolepis diminuta (3.3%). Among the highlights are protozoan Giardia lamblia (46.7%), Entamoeba coli (6.7%), E. histolytica /dispar (3.3%), Endolimax nana (3.3%) and Iodameba butschlii (3.3%). The high frequency of intestinal parasites and/or commensals in the neoplastic patients can be attributed to poor personal hygiene and lack of immunity to reinfection and poor knowledge of the prophylaxis of infection by protozoa and helminths. The results indicate the necessity of adopting a new criterion for neoplastic patients undergoing chemotherapy, primarily performing parasitological diagnosis, treatment and monitoring of cure of intestinal parasitic infections in this risk group.

O objetivo deste trabalho foi verificar a freqüência de parasitos e/ou comensais intestinais em pacientes neoplásicos submetidos à quimioterapia. As amostras de fezes foram analisadas pelo método de Lutz (1919) e Rugai (1954), em triplicata. O trabalho foi composto por três grupos, o primeiro (GI) formado por pacientes neoplásicos não submetidos à quimioterapia, o segundo (GII) formado por pacientes que estavam em tratamento quimioterápico, e o terceiro grupo (GIII) constituído por pacientes que terminaram a quimioterapia. Um total de 30 pacientes (GI –5, GII-18 e GIII-7) foram triados no Hospital Regional de Assis do Sistema Único de Saúde da cidade de Assis, São Paulo. Dados complementares sobre tratamento antiparasitário e tipo de tumor foram obtidos por questionário. A positividade foi de 66,7% (20 casos) para parasitos e/ou comensais intestinais. Os helmintos encontrados foram: Ascaris lumbricoides (36,7%), Ancilostomídeos (20%) e Hymenolepis diminuta (3,3%). Entre os protozoários destacaram-se: Giardia lamblia (46,7%), Entamoeba coli (6,7%), E. histolytica/E. dispar (3,3%), Endolimax nana (3,3%) e Iodameba butschlii (3,3%). A elevada freqüência de parasitos e/ou comensais intestinais em pacientes neoplásicos pode ser atribuída a higiene pessoal inadequada e ausência de imunidade a re-infecções e ao pouco conhecimento da profilaxia para infecção por protozoários e helmintos. Os resultados obtidos indicam a necessidade da adoção de um novo critério para os pacientes neoplásicos submetidos à quimioterapia realizando primeiramente diagnóstico parasitológico, tratamento e acompanhamento de cura das parasitoses intestinais neste grupo de risco.
Parasitic and intestinal commensals in the neoplastic patients undergoing chemotherapy
Keywords: Parasitic; Immunosuppression; Chemotherapy; Parasitoses; Imunossupressão; Quimioterapia